Influence of Different Pigment Incorporation Methods on the Sorption and Solubility of Medical Silicones - Nobrega, Adhara Smith; de Moraes Melo Neto, Clóvis Lamartine; de Magalhães Bertoz, André Pinheiro; de Melo Moreno, André Luiz; Goiato, Marcelo Coelho (European Journal of Dentistry, 2020)
Objective The aim of this study is to verify the influence of three pigment incorporation methods (conventional, mechanical, and industrial) on the sorption and solubility of the MDX4-4210 and A-2186 silicones.Materials and Methods The groups formed were based on the silicones used (A-2186 and MDX4-4210), intrinsic pigments (pink, bronze, and black), and pigment incorporation methods (conventional, mechanical, and industrial). The dimensions of all samples were 45-mm diameter (ø) × 1-mm thickness. Readings were taken initially and after 1,008 hours of aging.Statistical Analysis Three-way analysis of variance and the Tukey's test were performed (α = 0.05).Results For sorption and solubility, there was no difference between the incorporation methods for the A-2186 silicone, regardless of the pigment used (p > 0.05). For pink MDX4-4210, the industrial and mechanical methods showed higher values of sorption compared with the conventional method (p < 0.05). For bronze MDX4-4210, the industrial method showed a higher sorption value compared with the conventional and mechanical methods (p < 0.05). For black MDX4-4210, there was no difference between incorporation methods based on sorption (p > 0.05). For pink MDX4-4210, the mechanical method showed a higher solubility value compared with the industrial and conventional methods (p < 0.05). For black MDX4-4210 and bronze MDX4-4210, there was no statistically significant difference between incorporation methods based on solubility (p > 0.05).Conclusion Based on sorption and solubility, for the A-2186 silicone, the conventional, mechanical, and industrial methods of pigment incorporation were equivalent. For the MDX4-4210 silicone, its results of sorption and solubility were varied, and further studies are recommended.
Keywords: maxillofacial prosthesis; solubility; silicone elastomers; A-2186